The effects of trinexapac-ethyl on Pinus sylvestris and Picea abies - Bengtsson, Emil (SLU/Department of Plant Biology (from 140101), 2018)
The use of so-called micro-plant propagation have become a well-adapted cultivation technique in Swedish forestry nurseries. Although this production method has many advantages, a commonly occurring problem is that the young plants, after trans- plantation in the nursery, have an underdeveloped root system when the shoot part have reached desired length. Currently used methods to control the plant growth in a desired way involves long-night treatment and exposure to different stresses such as drought or nutrient deficiency. Unfortunately, long-night treatment requires expensive equipment and stressing might cause injury to the plants. Alternative methods to control plant growth are therefore sought after by the forestry industry.